Pendampingan Belajar Siswa dalam Memahami Operasi Penjumlahan Pecahan - Nur, Fitriani; Suharti; Angriani, Andi Dian; Andi Mattoliang, Lisnasari; A. Sriyanti (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2023)
Fractions are one of the mathematics materials at the elementary school level. Mathematics is still a difficult subject for students, especially in fraction addition operations. Therefore, some parents choose to bring in private teachers to help their children understand mathematics. This service is a learning assistance for students in Jeneponto district, South Sulawesi, which aims to train students to complete fraction addition operations through the media of fraction cards. This service was carried out by several lecturers of Mathematics Education at the Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar for 7 meetings, by making fraction card media to help students understand the concept of fractions, especially in fraction addition operations. The results of this dedication show that after participating in this community service activity, students can complete the operation of adding fractions. Another finding from this service is that there are still students who have not mastered the multiplication and division operations of integers, resulting in difficulties in completing fraction addition operations.